2011
DOI: 10.1186/1756-0500-4-273
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax phylogenetic structure in Northern Italy

Abstract: BackgroundAnthrax has almost disappeared from mainland Europe, except for the Mediterranean region where cases are still reported. In Central and South Italy, anthrax is enzootic, but in the North there are currently no high risk areas, with only sporadic cases having been registered in the last few decades. Regional genetic and molecular characterizations of anthrax in these regions are still lacking. To investigate the potential molecular diversity of Bacillus anthracis in Northern Italy, canonical Single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…It may be of interest to note that these zones, close to the mountainous massifs of France, share similar land topologies, made of pastoral valleys. Our data, consistent with other MLVA studies reporting new additional genotypes among Italian, Polish, and Swiss isolates (7)(8)(9)26) (33). The strains found in Europe (36,38) may represent old imported infections from Asia via animals or human activities, such as trading (33).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It may be of interest to note that these zones, close to the mountainous massifs of France, share similar land topologies, made of pastoral valleys. Our data, consistent with other MLVA studies reporting new additional genotypes among Italian, Polish, and Swiss isolates (7)(8)(9)26) (33). The strains found in Europe (36,38) may represent old imported infections from Asia via animals or human activities, such as trading (33).…”
Section: Discussionsupporting
confidence: 82%
“…This leads to a genotyping method that uses a set of 13 strategically placed canSNPs to subdivide B. anthracis isolates into three recognized major lineages (A, B, and C), with further subdivision into 12 clonal sublineages or subgroups (36). This method had been applied to analyze several collections of B. anthracis strains of worldwide origin (2,7,23,26,33,36). However, as it is based on TaqMan minor groove binding allelic discrimination assays, the current method incurs a high cost per studied marker.…”
mentioning
confidence: 99%
“…The genetic diversity of B. anthracis and geographic distribution of anthrax outbreaks in Italy was described by Fasanella et al [26], Lista et al [29] and Van Ert et al [24], and confirmed by Garofolo et al [31]. The dominant genotypes in Italy fell into the MLVA A1.a group and TEA SNP group.…”
Section: Introductionmentioning
confidence: 74%
“…It already was a deputy to the preparation of the two vaccines against anthrax, and Carbosap Pasteur [84], and prialla testing of new vaccine Sterne [85]. The center has the task to test the detection anthrax spores in suspicious samples (with the exception human clinical suspicion) as part of the emergency bioterrorism, which consists in the amplification nucleotide sequences specific for chromosome, the lethal factor, edema factor, the antigen and the protective capsule of Bacillus anthracis [86].…”
Section: Italian Overviewmentioning
confidence: 99%